Factores psicosociales y estado depresivo en estudiantes de la carrera de Psicología Clínica de la Universidad Técnica de Babahoyo periodo lectivo 2016 - 2017 - Alvarado Medina, Jimmy Leonardo (2017)
This research had as main objective to determine if the psychosocial factors produce depressive states in the students of the race of psychology of the technical university of Babahoyo in the academic period 2016-2017. The sample to be investigated corresponds to a total of 248 students of the aforementioned race, also worked with 5 teachers. The methodological design used in this research is exploratory, descriptive and explanatory. For data collection, a survey was conducted for the teachers of the institution and one addressed to the students of the school of psychology, as well as the inventory of depression of Aaron Beck applied only to the students. Once the investigation was concluded it was possible to verify that if there are psychosocial factors that produce discomfort in the students of the school of psychology as the intermittent depressive states, for which once the analysis and interpretation of data was completed, the proposal was elaborated to give A possible solution to the problematic and thus to improve the inappropriate behaviors in the students of the school of psychology